Method for producing polycarbonate resin composition pellets
Patent Information
- Application Number
- JP2024568815
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-11
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2044-06-11
AI Technical Summary
【0011】 本発明の製造方法によれば、高トルク密度で高スクリュー回転数の高エネルギー領域で二軸押出機によるポリカーボネート樹脂組成物ペレットを、高い生産性(高い吐出量)で安定的に製造することが可能となる。樹脂温度を下げることができるので、色調(YI)の悪化を防ぐことができ、透明性に優れたポリカーボネート樹脂材料を得ることができる。
Smart Images

Figure 0007652997000004 
Figure 0007652997000005 
Figure 0007652997000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing polycarbonate resin composition pellets, and more particularly to a method for producing polycarbonate resin composition pellets having excellent transparency with high productivity and more stably than conventional methods, using an ultra-high torque twin-screw extruder. [Background technology]
[0002] Polycarbonate resins are widely used in various fields because they have excellent impact resistance, heat resistance, electrical insulation, dimensional stability, etc., and a good balance of these properties. In particular, polycarbonate resins made from bisphenol compounds have the advantages of being transparent, impact resistance, and heat resistance, and being light and not easily broken, and are therefore used as a substitute for glass in automobile parts, building materials, and optical parts such as lenses. In recent years, they have also been widely used as molded products such as panel members for display devices used in various mobile terminals such as smartphones, tablet computers, car navigation systems, car audio systems, mobile game consoles, digital cameras, etc.
[0003] In order to mold these molded articles, polycarbonate resin composition pellets (pellets are those which are melted once and then shaped into cylindrical, spherical or elliptical shapes) in which various additives are blended with a polycarbonate resin raw material as necessary are used. Polycarbonate resin composition pellets are usually produced by a twin-screw extruder, and for many years, improvements in the plasticizing and kneading capabilities of twin-screw extruders have been desired in order to improve production capacity. Recently, the maximum torque density has reached 18 Nm / cm 3 Extruders with ultra-high torques reaching a torque of 1000 rpm (for example, the "TEXαIII" manufactured by Japan Steel Works, Ltd. and the "TEM-SX" manufactured by Shibaura Machine Co., Ltd.) have been developed, making it possible to produce in a high torque range that was not possible before. In addition, the high torque makes it possible to increase the screw rotation speed more than before, making it possible to operate in a high energy range (high torque density and high screw rotation speed), which makes it possible to obtain a high output that was not previously conceivable.
[0004] Regarding the torque density of the extruder, Patent Document 1 describes an invention that uses a single reverse screw element having a flight portion formed with an arc-shaped notch, for the purpose of increasing the productivity of glass fiber reinforced thermoplastic resin composition pellets compared to conventional methods and extremely reducing the probability that monofilament aggregates (unresolved glass fiber bundles) remain in the produced pellets. The conditions for this are: (i) a torque density, which is the value obtained by dividing the torque of the screw in the reverse screw element by the cube of the center distance between the meshing screws, of 11 Nm / cm 3 or more, and (ii) the Q / Ns density, obtained by dividing the discharge amount Q by the screw rotation speed Ns, by the cube of the center distance between the screws, is 0.013 kg / h / rpm / cm 3 The provisions state that:
[0005] However, in the paragraph
[0063] of Patent Document 1, regarding the torque density, it is stated that "the torque density is 11 (Nm / cm 3 ) or more, the filling rate of the material in the extruder increases, the energy density decreases, and the temperature rise is small even if the rotation speed is increased. The preferable torque density range is 13 Nm / cm 3 More than 18Nm / cm 3 The description simply states that the torque density is below 13.1 Nm / cm. In addition, in the examples of Patent Document 1, a twin-screw extruder "TEX44αII (manufactured by Japan Steel Works, Ltd.) with a screw element cylinder diameter D of 0.047 m" is used, but the allowable shaft torque density of the TEX44αII is 13.1 Nm / cm. 3 Above this, the screw shaft and gearbox will be damaged and the shaft will break, so it is usually operated at a torque density of 80% or less, so the torque density is at most 10.5Nm / cm 3 It is.
[0006] The above-mentioned twin-screw extruder with ultra-high torque density had not yet appeared on the market at the time of filing of Patent Document 1. Therefore, Patent Document 1 specifically discloses the conditions for a conventional low-torque extruder, and does not describe or suggest the various problems that arise during ultra-high torque operation that is the subject of the present invention, much less provide a solution to those problems. The torque density along the screw is highest at the base of the extruder, and this torque is used for melt mixing and conveying of the resin, and decreases toward the tip of the screw, reaching zero at the tip. Patent Document 1 describes the torque density in the reverse feed screw element in the glass fiber mixing section, but even in this section the screw shaft torque density is quite small, at 3 Nm / cm 3 The following is considered. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP2012-213997A Summary of the Invention [Problem to be solved by the invention]
[0008] Normally, in twin-screw extrusion, the resin is completely melted in the kneading section, devolatilized in the vacuum vent section, and extruded as strands from the die. However, compounding in a high-energy region causes the resin temperature to rise too high, which leads to poor color tone. The object (object) of the present invention has been made in consideration of such problems, and is to provide a method for producing polycarbonate resin pellets in a high energy region using an ultra-high torque twin-screw extruder, which lowers the resin temperature and prevents deterioration of color tone YI. [Means for solving the problem]
[0009] In order to achieve the above object, the present inventors have intensively studied methods for lowering the resin temperature, and have found that the viscosity-average molecular weight is 11,000 to 27,000 and the median diameter D 50The raw material is polycarbonate resin powder with a diameter of 400 to 1500 μm, and the screw shaft torque density is 9.0 to 17.0 Nm / cm 3 The screw speed is in the range of 400 to 800 rpm, and the discharge amount (kg / h) ÷ screw speed (rpm) ÷ the cube of the center distance between the shafts of the twin screws (cm 3 ) is 0.015~0.026kg / h / rpm / cm 3 It was found that by kneading under the above conditions and keeping the unmelted ratio in the range of 2-30%, i.e., intentionally leaving 2-30% of the unmelted portion after kneading, it is possible to significantly lower the resin temperature and suppress the increase in color tone YI. This effect can be explained as follows. Median diameter D 50 The glass transition temperature of polycarbonate resin powder particles with a diameter of 400 to 1500 μm is about 140°C. It is said that polycarbonate resin produced by the interface method has a partial crystalline structure, but its melting point is about 200°C, and it is said that it requires about 30 J / g of heat of fusion when melting. In other words, in a semi-molten state, its temperature is much lower than the surrounding molten polycarbonate, and it absorbs a lot of heat from the surroundings when it melts. In other words, it is like putting ice in hot water, and the temperature of the hot water drops rapidly. If there are few unmelted parts, the temperature of the surrounding molten polycarbonate cannot be lowered. Also, if there are too many unmelted parts, the unmelted parts accumulate in the die and mesh parts, preventing the resin from flowing and causing venting. If the unmelted rate is 2 to 30%, the unmelted parts will melt due to shearing at the breaker plate beyond the flange, retention in the die holder, and strong contraction and shearing at the die hole beyond that. Or, the strand will not break in the tiny unmelted parts that remain. The present invention relates to the following method for producing polycarbonate resin composition pellets.
[0010] 1. Viscosity average molecular weight is 11,000 to 27,000, and the median diameter D measured by the wet light scattering method 50 A method for producing polycarbonate resin composition pellets using polycarbonate resin powder particles having a diameter of 400 to 1500 μm as a raw material with a twin-screw extruder, The screw shaft torque density applied to the base of one screw is 9.0~17.0Nm / cm 3 The screw speed is in the range of 400 to 800 rpm, and the discharge rate (kg / h) ÷ screw speed (rpm) ÷ cube of the center distance between the twin screw shafts (cm 3 ) is 0.015~0.026kg / h / rpm / cm 3 The method for producing polycarbonate resin composition pellets comprises kneading the mixture under the above conditions, setting the unmelted rate at the flange portion upstream of the die holder in the range of 2 to 30%, and taking up strands extruded from the die and pelletizing them. 2. The manufacturing method described in 1 above, in which a vent having an opening with a length of 2.0 to 6.0D (D is the cylinder diameter) in the screw axial direction is used downstream of the kneading section to perform vacuum devolatilization, and the distance from the most downstream position of the vent opening to the tip of the screw is 5.0 to 10.0D. 3. The method according to claim 1 or 2, wherein the temperature of the strand immediately after leaving the die is in the range of 260 to 330°C. 4. The method according to any one of 1 to 3 above, wherein the polycarbonate resin composition pellets obtained have a total light transmittance of 50% or more as measured by transmitted light according to JIS K7361. Effect of the Invention
[0011] According to the production method of the present invention, it is possible to stably produce polycarbonate resin composition pellets with high productivity (high discharge amount) using a twin-screw extruder in a high energy region with high torque density and high screw rotation speed. Since the resin temperature can be lowered, deterioration of color tone (YI) can be prevented, and a polycarbonate resin material with excellent transparency can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a cross-sectional view showing an example of the vicinity of a die portion in a twin-screw extruder. [Diagram 2] FIG. 2 is a cross-sectional view showing the screw configuration of a twin-screw extruder used in the examples. [Diagram 3]1 is a photograph of a molten resin when a die holder is opened when measuring an undissolved rate in an example. [Figure 4] 4 is an image for measuring the unmelted rate of the molten resin in FIG. 3. [Diagram 5] In FIG. 4, this is an extracted image of the high brightness area. [Figure 6] This is an image binarized from the image in FIG. 5 in order to measure the area ratio of the unmelted part. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the present invention will be described in detail with reference to embodiments and examples, but the present invention should not be construed as being limited to the embodiments and examples.
[0014] The raw material used in the method for producing polycarbonate resin composition pellets of the present invention has a viscosity average molecular weight (Mv) of 11,000 to 27,000 and a median diameter D 50 The powder is made of polycarbonate resin granules having a particle size of 400 to 1500 μm. The polycarbonate resin powder refers to powder forms including, for example, flakes, granules, powders, and the like.
[0015] If the viscosity average molecular weight (Mv) is less than 11000, the strength of the resulting polycarbonate resin composition is weak, and if it is more than 27000, the resin temperature increases and the color tone deteriorates. The viscosity average molecular weight (Mv) is preferably 12000 or more, more preferably 13000 or more, and is preferably 26000 or less, more preferably 25000 or less, and further preferably 24000 or less.
[0016] Median diameter D of polycarbonate resin powder 50 However, if it is less than 400μm, the resin temperature will be too high and the color tone will deteriorate. If it is more than 1500μm, there will be a lot of unmelted material and it will be more likely to vent up. Median diameter D 50is preferably 450 μm or more, more preferably 500 μm or more, and is preferably 1400 μm or less, more preferably 1300 μm or less, and further preferably 1200 μm or less.
[0017] The particle size of polycarbonate resin powder is measured using a laser diffraction particle size distribution analyzer. 50 Specifically, it is a value measured using a laser diffraction particle size distribution analyzer "Mastersizer 3000" manufactured by Malvern Panalytical, using purified water as the dispersion medium and a surfactant as the dispersant, by the light scattering wet method. The measurement range is 0.01-3500 μm.
[0018] The particle size of polycarbonate resin powder can also be expressed as a particle size distribution measured according to JIS K0069 (dry sieving test method), and the median diameter D 50 The particle size according to this method is within the range of 400 to 1500 μm, preferably 450 to 1400 μm, and more preferably 500 to 1300 μm.
[0019] Such a median diameter D 50 The polycarbonate resin powder satisfying the above viscosity average molecular weight can be appropriately selected from commercially available products.
[0020] The polycarbonate resin powder may be 100% by mass of the polycarbonate resin raw material used as a raw material, or 50% by mass or more of the polycarbonate resin raw material used may satisfy the above viscosity average molecular weight and particle size. For example, as shown in the examples, it is also preferable to use the polycarbonate resin powder in combination with normal polycarbonate resin pellets having a larger particle size as a raw material. The amount of the polycarbonate resin powder is preferably more than 50% by mass, more preferably more than 60% by mass, more preferably more than 70% by mass, more preferably more than 80% by mass, more preferably more than 85% by mass, and even more preferably more than 90% by mass, more preferably more than 95% by mass.
[0021] [Polycarbonate resin] Examples of the polycarbonate resin include aromatic polycarbonate resins, aliphatic polycarbonate resins, and aromatic-aliphatic polycarbonate resins. Of these, aromatic polycarbonate resins are preferred. Specifically, aromatic polycarbonate polymers or copolymers obtained by reacting an aromatic dihydroxy compound with phosgene or a diester of carbonic acid are used.
[0022] Examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), tetramethylbisphenol A, α,α'-bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, and 4,4'-dihydroxydiphenyl.
[0023] Preferred examples of polycarbonate resins include polycarbonate resins using bisphenol A as a dihydroxy compound or a combination of bisphenol A and other aromatic dihydroxy compounds, and polycarbonate resins using bisphenol C or a combination of bisphenol C and other aromatic dihydroxy compounds (particularly bisphenol A).
[0024] The polycarbonate resin may be a homopolymer consisting of one type of repeating unit, or a copolymer having two or more types of repeating units, in which case the copolymer may be selected from various copolymer forms such as a random copolymer, a block copolymer, etc.
[0025] The viscosity average molecular weight (Mv) of a polycarbonate resin is a value calculated from the intrinsic viscosity ([η]) obtained by measuring the viscosity of a methylene chloride solution of the polycarbonate resin at 25°C using an Ubbelohde viscometer, and then using the following Schnell viscosity formula: [η]=1.23×10 -4 Mv 0.83
[0026] The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resins produced by either the phosgene method (interfacial polymerization method) or the melting method (ester exchange method) can be used. Polycarbonate resins produced by the interfacial polymerization method are suitable for the present invention because they are easy to obtain with a small color tone YI and are in the form of flakes during polymerization production. The color tone YI is preferably less than 2.0 by the method described below.
[0027] The polycarbonate resin may be not only virgin raw materials but also polycarbonate resin recycled from used products (so-called material recycled polycarbonate resin), and it is also preferable to contain both virgin raw materials and recycled resin, and it may be made of recycled polycarbonate resin. When using recycled polycarbonate resin, the proportion of recycled polycarbonate resin in the polycarbonate resin is preferably 40 mass% or more, 50 mass% or more, 60 mass% or more, or 80 mass% or more, and may be 100 mass%.
[0028] In the manufacturing method of the present invention, a twin-screw extruder is used. Various types of twin-screw extruders can be used, and the screw rotation method may be a co-rotating type or a counter-rotating type, but a co-rotating intermeshing type twin-screw extruder is particularly preferred. In addition, it is preferable to provide the twin-screw extruder with a vent port that is open to reduced pressure or the atmosphere.
[0029] In the present invention, the maximum torque density is preferably 16 to 20 Nm / cm 3 A twin-screw extruder with such an ultra-high torque is used, and the torque density of one of the screws at the base of the twin-screw extruder is 9.0 to 17.0 Nm / cm 3 This is carried out under the following conditions. The screw shaft torque density is defined as the torque Nm required to drive one screw (the torque applied to the base of the screw) divided by the cube of the center distance of the screw shaft, and is expressed in Nm / cm. 3Even if extrusion is performed using extruders of different sizes, if the torque density value is the same, the torque applied to the resin per unit volume will be the same. The motor that drives the screw generates torque (Nm), which is transmitted to the screw shaft and performs the work of transporting and melting the polycarbonate resin. This torque represents the strength of the torque applied to the base of the screw shaft. The value of the torque decreases as it progresses toward the tip of the screw, and the torque at the tip of the screw is 0 Nm. The torque generated by the motor that drives the extruder screw is displayed on the extruder control panel in % units relative to 100% of the screw allowable torque. For example, in the case of TEX44αIII, 100% torque is a torque density of 17.9 Nm / cm 3 Since this is equivalent to 100% torque, the torque density can be calculated from the displayed % during operation. Also, with general VVVF inverter control, in the constant torque region, the current value (A) divided by the rated current corresponds to the torque %. The maximum torque of the TEX44αIII (total torque applied to the base of the two screw shafts) is 2077Nm, and since the distance between the two screw shafts is 3.87cm, the maximum torque density of one screw (base part) is 17.9Nm / cm 3 It becomes.
[0030] Raw materials such as polycarbonate resin powder are fed from the feed port at the base of the extruder, fed, conveyed and preheated in the feed / convey / preheat section, then melted and kneaded in the kneading section and conveyed.
[0031] The screw configuration is as follows: from the base of the extruder toward the direction of raw material feed, the supply, transport and preheating section is made up of a full-flight transport screw, the kneading section, and a full-flight screw for transporting after melting, and a vacuum vent is preferably provided in the part of the full-flight screw after the kneading section. This vacuum vent removes volatile components in the molten resin, i.e. moisture, residual solvent, volatile components of additives, etc.
[0032] The kneading section is not particularly limited in its configuration, but is preferably configured to have a length of 2.5D to 8.0D (D is the cylinder diameter) that combines two or more of R kneading discs, N kneading discs, L kneading discs, L screws, seal rings, mixing screws, or rotor screws. This kneading section may be installed in two or more locations as long as the total length is 2.5D to 8.0D.
[0033] The R kneading disc is also called the progressive kneading disc (hereinafter sometimes referred to as R), and usually has two or more blades with a twist angle Θ of 10 degrees to 75 degrees. By setting the blades at a specified angle in this way, it is possible to feed the resin and apply a strong shearing force. The N kneading disc is also called the orthogonal kneading disc (hereinafter sometimes referred to as N), and usually has two or more blades, with the twist angle Θ of the blade being 75 degrees to 105 degrees. Because the blades are set at approximately 90 degrees offset, there is almost no force to send the resin, but the kneading force is strong. The L kneading disc is also called the reverse kneading disc (hereinafter sometimes referred to as L), and usually has two or more blades with a twist angle Θ of -10 degrees to -75 degrees. The L kneading disc is an element with the ability to block incoming resin or to boost pressure by acting in the direction of returning the resin that has been fed. By installing it downstream of the element that promotes kneading, it blocks the resin and exerts a strong kneading effect. The L screw, also known as the reverse feed screw, is a screw that spirals in the opposite direction to the normal feed screw, and is an element that has the ability to block resin and increase pressure in the direction that returns the fed resin. Like the L kneading disc, it blocks resin by being installed downstream of the element that promotes kneading, and exerts a strong kneading effect.
[0034] The above-mentioned blades are usually elliptical, with flat parts at the two vertices of the ellipse. These blades are also called disks, and each kneading disk is usually composed of 3 to 7 disks. These disks may be roughly triangular and have three vertices, which are also called three-row kneading disks. Similarly, there are R, N, and L types. These can also be used in the same way. Among the kneading disks, there are also twist kneading disks, whose vertices are twisted in the screw axial direction, and similar kneading effects can be obtained. Median diameter D 50 In order to efficiently melt polycarbonate resin powder particles having a diameter of 400 to 1500 μm, a twist kneading disk is preferably used.
[0035] The seal ring is a ring-shaped device that is fitted to the screw, and blocks about 70-90% of the flow path, retaining the resin flow and increasing the resin pressure. As with L kneading, by installing it downstream of the element that promotes kneading, the resin is blocked, providing a powerful kneading effect. A mixing screw is made by cutting the crest of a screw flight, and is a single- or double-start or reverse-start screw that has a strong shear dispersion force. There are forward-start notch type mixing screws and reverse-start notch type mixing screws. The rotor screw has elliptical (two-blade structure) or triangular rotor blades, and can generate strong shear force due to the gap (tip clearance) between the rotor and the inner wall surface of the barrel.
[0036] It is preferable that the kneading section is a combination of two or more of the above-mentioned ones, but a combination of an R kneading disc, an N kneading disc, and an L kneading disc is more preferable. For example, a configuration in which one or more Rs are followed by multiple Ns and then Ls, such as RRNNNNNL, or a configuration such as RNNNL, is preferable.
[0037] In the method of the present invention, the torque density applied to the screw shaft is 9.0 to 17.0 Nm / cm 3 The high torque and high screw rotation of 400 to 800 rpm enable extrusion of unprecedented high throughput. The screw rotation speed is less than 400 rpm, and the torque density is 9.0 Nm / cm 3 If the torque density is less than 17.0 Nm / cm, high discharge cannot be obtained. 3 If the screw rotation speed exceeds 800 rpm, the screw shaft may be damaged by even a slight torque fluctuation. If the screw rotation speed exceeds 800 rpm, the resin temperature rises rapidly, leading to an increase in YI and a deterioration in total light transmittance. In order to produce polycarbonate resin composition pellets with excellent transparency at high discharge (high productivity), the screw rotation speed should be in the range of 400 to 800 rpm and the torque density should be 9.0 to 17.0 Nm / cm. 3 must be in the range.
[0038] In the present invention, the screw shaft torque density is 9.0 to 17.0 Nm / cm 3 The screw speed is in the range of 400 to 800 rpm, and the discharge rate (kg / h) ÷ screw speed (rpm) ÷ cube of the center distance between the twin screw shafts (cm 3 )] to 0.015-0.026 kg / h / rpm / cm 3 A specific polycarbonate resin raw material is used and kneaded under the above conditions, so that the unmelted portion of the polycarbonate resin composition after kneading is 2 to 30%, which makes it possible to significantly lower the resin temperature and suppress an increase in color tone YI. [Discharge rate (kg / h) ÷ screw rotation speed (rpm) ÷ cube of the center distance between the twin screw shafts (cm 3 )] is preferably 0.016 to 0.025 kg / h / rpm / cm 3 and more preferably 0.017 to 0.024 kg / h / rpm / cm 3 It is.
[0039] Screw shaft torque density is 9.0~17.0Nm / cm 3 However, preferably 9.5 Nm / cm 3More preferably, 10.0 Nm / cm 3 Above, 10.5Nm / cm 3 More preferably, it is 16.5 Nm / cm or more. 3 Less than or equal to 16.0 Nm / cm 3 The following is the result.
[0040] As shown in Figure 1, a twin-screw extruder has a die holder 4 attached via a flange 3 to the tip 2 of a cylinder that houses two screws 1, 1'. The die section has a breaker plate (or ring plate) 5, and a screen mesh can be installed inside the breaker plate 5 to filter out foreign matter. If a screen mesh is not used, it is common to install a ring-shaped plate called a ring plate. The die holder 4 is also called the die plate, and the flange 3 is also called the hinge plate. A die 6 having a die hole 7 is built into the die holder 4.
[0041] The proportion (%) of the unmelted portion of the polycarbonate resin composition after kneading can be confirmed as the unmelted rate in the inside A of the flange 3 in front of the die holder 4. Specifically, after melt-kneading under the above conditions, the die holder 4 of the extruder is opened by the hinge of the flange 3, and the molten resin in the inside A of the flange 3 is allowed to drip downward. When the vent is then suctioned by vacuum, the molten portion appears transparent, and the unmelted portion appears cloudy. At this time, no force is applied to the resin, and the resin coming out of the inside of the flange 3 is allowed to fall naturally. Since the unmelted portion remains as a cloudy portion, a photograph is taken from the front of the tips of the two screws within a field of view that allows the entire rotating left and right screws 1 and 1' to be seen. The photograph is enlarged so that the molten portion and the unmelted portion of the photograph are displayed in full screen.
[0042] Fig. 3 is a photograph showing this state, and is a photograph of the molten resin when it is released to measure the undissolved rate in the examples. The die holder 4 is pulled forward in Fig. 3 by the hinge on the side of the flange 3, and the part of the resin dripping down from the die holder 4, enclosed by the white dashed line in Fig. 3, is photographed to obtain an image as shown in Fig. 4. This image is analyzed to determine the visual area ratio of the unmelted parts from the transparent melted parts and the unmelted opaque parts, and the unmelted ratio (unmelted visual area ratio: unit: %) is measured.
[0043] Specifically, the image analysis was carried out as follows. Using the general-purpose image analysis and measurement system "WinROOF2018" (Mitani Shoji Co., Ltd.), a monochrome image as shown in Figure 4 was created, and using the density conversion function, the threshold density was set to 67 to 255 to extract the highly bright parts (Figure 5). After that, it was binarized to select the cloudy parts (unmelted parts) with a threshold value of 63 to 225 (Figure 6), and the visual field area ratio of the unmelted parts was measured from this. This unmelted field area ratio is not the unmelted volume ratio "unmelted part volume / (melted part volume+unmelted part volume)". The melted part is transparent, and both the unmelted part on the surface and the unmelted part inside are visible. Therefore, the unmelted field area ratio is larger than the unmelted volume ratio, but in the present invention, the unmelted field area ratio measured by the above-mentioned method is used as the unmelted ratio.
[0044] The unmelted ratio is 2 to 30%, but is preferably 3% or more, more preferably 4% or more, and is preferably 25% or less, more preferably 20% or less. By leaving 2% to 30% of the unmelted portion, it is possible to significantly lower the resin temperature and suppress an increase in color tone YI. If the unmelted ratio is less than 2%, the YI is poor and the transparency is insufficient, and if it exceeds 30%, venting up occurs rapidly, making it easy for production to become impossible.
[0045] In order to stably produce polycarbonate resin composition pellets having excellent transparency in the above-mentioned high energy region, it is preferable to optimize the cylinder configuration. Polycarbonate resin absorbs about 0.2% moisture in a high humidity environment. In addition, a solvent is used in the manufacturing process, and even if it is dried in a subsequent process, a small amount of the solvent remains. Usually, the remaining solvent is 0.1% or less. Such moisture and remaining solvent are vaporized in the high temperature / molten state in the twin-screw extruder, and the volatile components are removed from the vacuum vent, but the more the amount of polycarbonate resin processed, the greater the amount of the volatile components. Then, an upward air current due to a large amount of volatile components is generated in the vacuum vent, and vent-up, which pushes up the molten resin, is likely to occur.
[0046] In order to suppress this vent-up, it is possible to further suppress it by using a vent cylinder having an opening with a screw axial length of 2.0 to 6.0D downstream of the kneading section to perform devolatilization. If it is shorter than 2.0D, devolatilization is insufficient, and vent-up is likely to occur from the upstream of the vacuum vent. If it is longer than 6.0D, the extruder becomes longer overall, the residence time becomes longer, the resin temperature increases, and the YI increases. In addition, the width of the opening of the vacuum vent (the length of the width perpendicular to the screw) is preferably 0.3 to 1.5D. If it is less than 0.3D, the devolatilization ability is low and vent-up is likely to occur. If it is more than 1.5D, vent-up may occur due to the centrifugal force of the resin rotating on the screw. The cylinder, sometimes called a barrel, is the same thing, although the name may vary depending on the extruder manufacturer. The cylinder diameter is the diameter of the cylinder where the holes do not intersect, as the two cylinders on the left and right intersect. Here, 1D refers to the cylinder diameter.
[0047] In addition, in this high energy region, i.e., in the high discharge region, the distance from the most downstream position of the vent opening to the tip of the screw is preferably 5.0 to 10.0D. If it is shorter than this, the resin retention part at the tip of the screw will reach the vacuum vent due to the pressure at the die hole or mesh screen, and vent-up will easily occur. In this case, vent-up occurs when the resin rises from the downstream of the screw to the vent part. If it is longer than this, the retention time will be longer, the resin temperature will rise, and YI will easily increase.
[0048] The extruded strand-like molten polycarbonate resin composition is then cooled, preferably in water, and cut into pellets. The shape of the extrusion die 6 is not particularly limited, and a known one may be used. The diameter of the die hole 7 of the discharge nozzle is usually about 2 to 5 mm, depending on the extrusion pressure and the desired pellet size. The temperature of the polycarbonate resin composition immediately after extrusion is preferably 260 to 330°C, more preferably 265 to 325°C.
[0049] In the method of the present invention, the viscosity average molecular weight is 11,000 to 27,000, the median diameter D 50 A raw material containing preferably 50% by mass or more of polycarbonate resin powder particles having a diameter of 400 to 1500 μm is used, but other resins and additives may be blended in. Such blending components can be fed from a feed port at the base of the twin-screw extruder together with the polycarbonate resin powder particles or as a separate feed, or can be added from the middle of a divided kneading section. Preferred examples of other blending components include other resins, flame retardants such as phosphorus-based flame retardants and organometallic salt-based flame retardants, flame retardant assistants such as fluororesin (PTFE), various elastomers (impact resistance improvers), release agents, stabilizers, fillers (filling materials), reinforcing agents, colorants (dyes and pigments), ultraviolet absorbers, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, and antibacterial agents.
[0050] Alternatively, polycarbonate resin pellets may be used. The pellets usually have a length of 2 to 5 mm and a thickness (diameter) of 2 to 5 mm. The weight ranges from 10 to 40 mg per pellet. The polycarbonate resin pellets may be unused so-called virgin pellets, or recycled material (regenerated material) pellets. Preferred examples of raw materials for recycled material pellets include optical disks such as CDs and DVDs, light guide plates, automobile window glass, automobile headlamp lenses, vehicle transparent parts such as windshields, containers such as water bottles, eyeglass lenses, soundproof walls, glass windows, and building parts such as corrugated sheets. In addition, crushed products obtained from non-conforming products, sprues, or runners during molding, or crushed, washed, separated, and recovered from these, may be repelletized.
[0051] The polycarbonate resin composition pellets obtained by the method of the present invention have excellent transparency, and the total light transmittance (2 mm thickness) measured by transmitted light according to JIS K7361 is preferably 50% or more, more preferably 60% or more, even more preferably 65% or more, and particularly preferably 70% or more.
[0052] The method for producing a molded article from the polycarbonate resin composition pellets obtained by the method of the present invention is not particularly limited, and any molding method generally used for polycarbonate resins, such as general injection molding, ultra-high speed injection molding, injection compression molding, multi-color injection molding, gas-assisted injection molding, molding using an insulated mold, molding using a rapid heating and cooling mold, foam molding (including supercritical fluids), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, etc. can be used.
[0053] The obtained molded article can be suitably used as parts for office automation equipment such as printers and copiers, electrical equipment, electronic equipment, vehicles such as automobiles, houses, buildings, and other structures, and can be particularly suitably used as housings for office automation equipment such as printers and copiers, computers, personal computers, various mobile terminals, batteries, and the like. EXAMPLES
[0054] The present invention will be described in more detail below with reference to examples, but the present invention should not be construed as being limited to the following examples.
[0055] The extruder used in the examples and comparative examples was a twin-screw extruder "TEX44αIII" with ultra-high torque manufactured by Japan Steel Works, Ltd. The center distance of the screw shafts was 3.87 cm, and the maximum torque (the sum of the torques applied to the roots of the two screw shafts) was 2077 Nm. The screw configurations used were those shown in cylinder configurations 1 to 3 in Figure 2. All kneading sections were configured with five sets of kneading disks RRNNL. Each kneading disk had five blades and a length of 0.936D. 1D had a cylinder diameter of 47 mm.
[0056] The cylinder configurations are cylinder configurations 1 to 3 shown in FIG. <Cylinder configuration 1> The cylinder position C1 was a hopper cylinder, C2 to C11 were intermediate cylinders (cylinders without openings), C12 was a vent cylinder with a long opening (opening length 4D, opening width 1D), and C13 to C14 were intermediate cylinders. <Cylinder configuration 2> C1 was a hopper cylinder, C2 to C12 were intermediate cylinders, C13 was a vent cylinder with a long opening (opening length 4D, opening width 1D), and C14 was an intermediate cylinder. <Cylinder configuration 3> C1 was the hopper cylinder, C2 to C12 were intermediate cylinders, C13 was a normal vent cylinder (opening length 1D, opening width 1D), and C14 to C15 were intermediate cylinders.
[0057] A 40-mesh screen mesh was installed inside the breaker plate 5. The die 6 used had 17 holes with a hole diameter of 4.5 mmφ and a land length L of 16 mm.
[0058] (Examples 1 to 7, Comparative Examples 1 to 2) The raw material used had a viscosity average molecular weight Mv of 14,200 and a median diameter D 50 The polycarbonate resin powder with a diameter of 574 μm ("H-7000" manufactured by Mitsubishi Engineering Plastics Corporation, hereinafter referred to as PC-1) was used. 50 was 620 μm.
[0059] Example 1 The cylinder configuration was cylinder configuration 1, and the cylinder temperature settings were 70°C for cylinder position C2, 250°C for C3 to C14, and 250°C for the flange and die holder. The screw rotation speed was set to 700 rpm, and PC-1 was fed to the hopper cylinder of C1 at a processing rate (same as the discharge rate) of 850 kg / h. The cube of the discharge rate / rotation speed / axis distance was 0.021 kg / h / rpm / cm. 3 The mixture was kneaded under the following conditions. The screw shaft torque density was calculated from the motor torque (torque %) displayed on the control panel at this time. When the die holder 4 was opened by the hinge of the flange 3 and suctioned by vacuum, unmelted, cloudy polycarbonate resin was observed in the transparent polycarbonate resin molten in the flange 3 in front of the die holder 4. This molten and unmelted polycarbonate resin naturally fell and accumulated in a water-filled tray placed below, and was removed each time about 10 kg was accumulated. The tips of the two screws were visible from the opened die holder, and the parts were photographed and enlarged, and the unmelted field area ratio (hereinafter referred to as the unmelted ratio (%)) was calculated by the image analysis described above, and is shown in Table 1. The feed and screw rotation were once stopped, the die holder was closed, and the operation was continued under the same conditions to extrude a strand, which was then taken up using a cooling water tank and cut with a pelletizer to obtain pellets. The pellets obtained were injection molded to determine the total light transmittance and YI. The temperature of the strand emerging from the die was measured with a thermocouple and taken as the resin temperature.
[0060] The total light transmittance was measured according to JIS K7361 by drying the above resin composition pellets at 100°C for 5 hours, and then injection molding a three-level plate (90 mm x 50 mm x thicknesses of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side) using an injection molding machine ("J55-60H" manufactured by Japan Steel Works, Ltd.) at a cylinder setting temperature of 280°C, a mold temperature of 70°C, a screw rotation speed of 100 rpm, and an injection speed of 25 mm / s. The total light transmittance (unit: %) of the 2 mm-thick portion of the obtained three-level plate was measured using an NDH-2000 type haze meter manufactured by Nippon Denshoku Industries Co., Ltd.
[0061] In addition, the YI was measured at the same location using a Nippon Denshoku Corporation spectrophotometer "SE6000" with transmitted light.
[0062] Based on the above results, an overall evaluation was conducted using the following three-level criteria (◯, △, ×). ◯: The YI measured at a thickness of 2 mm is less than 2.0, and there are no problems in production. △: The YI measured at a thickness of 2 mm is less than 2.0, making continuous production difficult. ×: YI measured at 2 mm thickness is 2.0 or more, or production is not possible. The results are shown in Table 1.
[0063] Examples 2 to 5 The experiment was carried out in the same manner as in Example 1, except that the screw rotation speed, discharge amount, and the cube of the discharge amount / rotation speed / axis distance were set as shown in Table 1.
[0064] Example 6 The experiment was conducted in the same manner as in Example 1, except that the cylinder configuration was changed to cylinder configuration 2. When the vacuum vent port was checked, it was confirmed that the resin was gradually rising from the area downstream of the screw. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. After a long period of operation, the vacuum vent port was blocked and it was necessary to stop the extruder. Since the resin gradually vented from the area downstream of the screw, it is believed that the resin was retained at the tip of the screw due to the resin pressure in the die hole and mesh, causing the resin to vent.
[0065] Example 7 The experiment was conducted in the same manner as in Example 1, except that the cylinder configuration was changed to cylinder configuration 3. When the vacuum vent port was checked, it was confirmed that the resin was gradually vented up from the region upstream of the screw, although only slightly. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. After a long period of operation, the vacuum vent port became clogged, and the extruder had to be stopped. Since the resin was gradually vented up from the region upstream of the screw, it is believed that a large amount of volatile components were released from the resin, and that the volatile components rose quickly in a normal vent with a narrow opening, causing the resin to vent up gradually.
[0066] Comparative Example 1 The experiment was conducted in the same manner as in Example 1, except that the screw rotation speed, discharge rate, and the cube of discharge rate / rotation speed / axis distance were set as the conditions in Table 1. The unmelted rate when the die holder was opened was as high as 33%. When the die holder was closed and the strand was pulled out, venting occurred rapidly from the upstream of the screw, and the extruder had to be stopped. There was no time to sample the pellets. It is believed that there were many unmelted parts, which were blocked by the mesh, causing the resin to remain in a long area at the tip of the screw, causing the rapid venting.
[0067] Comparative Example 2 The experiment was conducted in the same manner as in Example 1, except that the screw rotation speed, discharge rate, and the cube of discharge rate / rotation speed / axis distance were set as the conditions in Table 1. When the die holder was opened, no unmelted parts were found (unmelted rate: 0%). The die holder was closed, and the strand was taken up and cut to obtain pellets. The temperature of the strand was high, and the YI of the injection molded piece was also high. It is believed that the absence of unmelted parts allowed the resin temperature to easily rise, causing the color tone to deteriorate. The results are shown in Table 1 below.
[0068] [Table 1]
[0069] (Examples 8 to 14, Comparative Examples 3 to 4) The raw material used had a viscosity average molecular weight Mv of 21,500 and a median diameter D 50 The polycarbonate resin powder with a diameter of 1060 μm ("S-3000" manufactured by Mitsubishi Engineering Plastics Corporation, hereafter referred to as PC-2) was used. 50 was 1150 μm. Example 8 The experiment was carried out in the same manner as in Example 1, except that the polycarbonate PC-2 was used instead of the polycarbonate PC-1.
[0070] Examples 9 to 12 The experiment was conducted in the same manner as in Example 8, except that the screw rotation speed, discharge amount, and the cube of the discharge amount / rotation speed / axis distance were set as shown in Table 2.
[0071] Example 13 The experiment was conducted in the same manner as in Example 8, except that the cylinder configuration was changed to cylinder configuration 2. When the vacuum vent port was checked, it was confirmed that the resin was gradually rising from the area downstream of the screw. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. After a long period of operation, the vacuum vent port was clogged and the extruder had to be stopped. Since the resin gradually vented from the area downstream of the screw, it is believed that the resin was retained at the tip of the screw due to the resin pressure in the die hole and mesh, causing the resin to vent.
[0072] Example 14 The experiment was conducted in the same manner as in Example 8, except that the cylinder configuration was changed to cylinder configuration 3. When the vacuum vent port was checked, it was confirmed that the resin was gradually vented up, with a small amount of resin rising from the region upstream of the screw. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. After a long period of operation, the vacuum vent port became clogged, and the extruder had to be stopped. Since the resin vented up gradually from the region upstream of the screw, it is believed that there was a large amount of volatile components from the resin, and that the volatile components rose quickly and vented up gradually in a normal vent with a narrow opening.
[0073] Comparative Example 3 The experiment was conducted in the same manner as in Example 8, except that the screw speed, discharge rate, and the cube of discharge rate / speed / axis distance were set as the conditions in Table 2. The unmelted rate when the die holder was opened was as high as 32%. When the die holder was closed and the strand was pulled out, venting occurred rapidly from the upstream of the screw, and the extruder had to be stopped. There was no time to sample the pellets. It is believed that there were many unmelted parts, which were blocked by the mesh, causing the resin to remain in a long area at the tip of the screw, causing the rapid venting.
[0074] Comparative Example 4 The experiment was conducted in the same manner as in Example 8, except that the screw rotation speed, discharge rate, and the cube of discharge rate / rotation speed / axis distance were set as the conditions in Table 2. When the die holder was opened, no unmelted parts were found (unmelted rate: 0%). The die holder was closed, and the strand was taken up and cut to obtain pellets. The temperature of the strand was high, and the YI of the injection molded piece was also high. It is believed that the absence of unmelted parts allowed the resin temperature to easily rise, causing the color tone to deteriorate. The results are shown in Table 2 below.
[0075] [Table 2]
[0076] (Examples 15 to 21, Comparative Examples 5 to 7) The raw material was a mixture of 80% by mass of PC-2 and 20% by mass of pellets of polycarbonate resin with a viscosity average molecular weight of 20,800 ("M7020IR" manufactured by Mitsubishi Engineering Plastics Corporation) (pellet diameter 3 mm, pellet length 3 mm, average weight 20 mg / piece; hereafter referred to as PC-3). Example 15 The experiment was carried out in the same manner as in Example 1, except that the polycarbonate resin PC-1 was changed to 80 mass % (680 kg / h) of PC-2 and 20 mass % (170 kg / h) of PC-3.
[0077] Examples 16 to 19 An experiment was conducted in the same manner as in Example 15, except that the screw rotation speed, discharge amount, and the cube of the discharge amount / rotation speed / axis distance were set as shown in Table 3.
[0078] Example 20 The experiment was conducted in the same manner as in Example 15, except that the cylinder configuration was changed to cylinder configuration 2. When the vacuum vent port was checked, it was confirmed that the resin was gradually rising from the area downstream of the screw. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. When operated for a long time, the vacuum vent port was clogged and it was necessary to stop the extruder. Since the resin gradually vented from the area downstream of the screw, it is thought that the resin was retained at the tip of the screw due to the resin pressure in the die hole and mesh, causing the resin to vent up.
[0079] Example 21 The experiment was conducted in the same manner as in Example 15, except that the cylinder configuration was changed to cylinder configuration 3. When the vacuum vent port was checked, it was confirmed that the resin was gradually vented up from the region upstream of the screw, although only slightly. The strand was immediately pulled, cut with a pelletizer, and pellets were sampled in a short time. After a long period of operation, the vacuum vent port became clogged, and the extruder had to be stopped. Since the resin was gradually vented up from the region upstream of the screw, it is believed that there was a large amount of volatile components from the resin, and that the volatile components rose quickly and vented up gradually in a normal vent with a narrow opening.
[0080] Comparative Example 5 The experiment was conducted in the same manner as in Example 15, except that the screw rotation speed, discharge rate, and the cube of discharge rate / rotation speed / axis distance were set as the conditions in Table 3. The unmelted rate when the die holder was opened was as high as 36%. When the die holder was closed and the strand was pulled out, venting occurred rapidly from the upstream of the screw, and the extruder had to be stopped. There was no time to sample the PET. It is believed that there were many unmelted parts, which were blocked by the mesh, causing the resin to remain in a long range at the tip of the screw, causing the rapid venting.
[0081] Comparative Example 6 The experiment was conducted in the same manner as in Example 15, except that the screw rotation speed, discharge rate, and the cube of discharge rate / rotation speed / axis distance were set as the conditions in Table 3. When the die holder was opened, no unmelted parts were found (unmelted rate: 0%). The die holder was closed, and the strand was taken and cut to obtain pellets. The temperature of the strand was high, and the YI of the injection molded piece was also high. It is believed that the absence of unmelted parts allowed the resin temperature to easily rise, causing the color tone to deteriorate.
[0082] Comparative Example 7 The experiment was conducted in the same manner as in Example 19, except that 100% by mass of PC-3 was used as the raw material. The unmelted rate when the die holder was opened was as high as 35%. When the die holder was closed and the strand was pulled out, venting occurred rapidly from the upstream of the screw, and the extruder had to be stopped. There was no time to sample the PET. It is believed that there were many unmelted parts, which were blocked by the mesh, and the resin was retained in a long range at the tip of the screw, causing rapid venting, and it is understood that the pellets are difficult to melt. The results are shown in Table 3 below.
[0083] [Table 3] [Industrial Applicability]
[0084] INDUSTRIAL APPLICABILITY According to the method of the present invention, polycarbonate resin composition pellets having excellent transparency can be produced with high productivity and more stably than conventional methods using an ultra-high torque twin-screw extruder, and therefore the method has extremely high industrial applicability. [Explanation of symbols]
[0085] 1, 1': Screw 2: Tip of the extruder cylinder 3: Flange 4: Die holder 5: Breaker plate 6: Die 7: Die hole A: Measurement area for unmelted resin rate in flange 3
Claims
1. Viscosity average molecular weight is 11,000 to 27,000, and the median diameter D measured by the wet light scattering method 50 A method for producing polycarbonate resin composition pellets using polycarbonate resin powder particles having a particle size of 400 to 1500 μm as a raw material with a twin-screw extruder, comprising the steps of: The screw shaft torque density applied to the base of one screw is 9.0 to 17.0 Nm / cm 3 The screw speed is in the range of 400 to 800 rpm, and the discharge rate (kg / h) ÷ screw speed (rpm) ÷ cube of the center distance between the twin screw shafts (cm 3 ) is 0.015 to 0.026 kg / h / rpm / cm 3 The method for producing polycarbonate resin composition pellets comprises kneading the mixture under the above conditions, setting the unmelted ratio at the flange portion before the die holder in the range of 2 to 30%, and taking up strands extruded from the die and pelletizing them.
2. The method according to claim 1, wherein the devolatilization is carried out in vacuum using a vent having an opening downstream of the kneading section and a length of 2.0 to 6.0 D (D is a cylinder diameter) in the screw axial direction, and the distance from the most downstream position of the vent opening to the tip of the screw is 5.0 to 10.0 D.
3. The method according to claim 1 or 2, wherein the temperature of the strand immediately after leaving the die is in the range of 260 to 330°C.
4. The method according to any one of claims 1 to 3, wherein the polycarbonate resin composition pellets obtained have a total light transmittance of 50% or more as determined by transmitted light according to JIS K7361.
Citation Information
Patent Citations
Manufacture of polycarbonate resin pellet
JP1997066524A
Method for producing flame-retardant polycarbonate resin composition
JP2003073484A
Method for manufacturing resin pellet
JP2020040356A
Method for producing flame retardant polycarbonate resin composition pellets
WO2023089929A1
Method of manufacturing glass fiber reinforced thermoplastic resin composition pellet
JP2012213997A